Antibacterial Effects of Green Betel (Piper betle Linn.) Leaf Against Streptococcus agalactiae and Escherichia coli - Puguh Surjowardojo; Endang Setyowati; Ike Ambarwati (AGRIVITA, Journal of Agricultural Science, 2019)
This study investigated the effect of betel (Piper betle L.) leaf at two physiological ages (young, 3rd leaf, and old, 8th leaf) at three concentrations of crude boiled-water extracts (10%, 20%, and 30%) against Streptococcus agalactiae and Escherichia coli. A completely randomized design with nesting was adopted for the six treatments and six replicates. The inhibition zone on nutrient agar media was measured. Overall there were no significantly differences. However, the inhibition zone diameters with 10%, 20%, and 30% crude water extracts of young leaves with S. agalactiae were 5.18 ± 0.99, 5.96 ± 0.34, and 6.38 ± 1.52 mm, respectively, and for old leaves, they were 5.76 ± 0.62, 5.67 ± 0.43, and 4.68 ± 0.33 mm, respectively. For E. coli, the corresponding values for young leaves were 3.96 ± 1.45, 4.54 ± 0.72, and 3.51 ± 0.48 mm, respectively, and for old leaves, the values were 3.85 ± 1.20, 4.14 ±0.68, and 2.35 ± 0.83 mm, respectively. The strongest inhibition was shown by the 30% crude water extract of young leaves against S. agalactiae.